PRACTICE OF POWER OF MEDICAL AUTHORITY OF THE MENTAL HOSPITAL ON THE PSYCHIATRIC PATIENT WITH STIGMA - Putro, Bambang Dharwiyanto; Kumbara, AA Ngurah Anom; Wirawan, A.A. Bagus (E-Journal of Cultural Studies, 2018)
The matters pertaining to mental disorders are complex as they are not only related to the medical professionalism, patients, their families and society but they are also related to the stigma they have and the protection of their dignity and status. Stigma is like a prison in the social relation constructed by the apparatuses that contribute to development, the regime of knowledge, and modernism on behalf of normalization. By applying the point of view of cultural studies, namely siding with those who are suppressed, this present study is intended to identify the form of the stigma which the psychiatric patients have resulting from the practice of power of the medical authority implemented by the Mental Hospital. Observation and in-depth interview methods were employed in the present study. The data were collected through life story and library research. The collected data were analyzed descriptively, qualitatively and interpretatively using the relevant critical theories such as the theory of discourse, the theory of deconstruction, and the theory of hegemony. The result of the study shows that there are two forms of the stigma which the psychiatric patients suffer from; they are the public stigma (the stigma brought about by society) and the self-stigma (the stigma brought about the patients and their families). The factors which contribute to the stigma of mental disorders can be classified into two; they are the external and internal factors as the translation of the hegemony of power and the domination of the authority of social and medical apparatus over the psychiatric patients leading to the social and identity gap. This shows the form of the struggle involving power in order to strengthen the domination of the apparatus in different aspects of life. The psychiatric patients cannot speak and are so marginalized that they have almost never been heard. The society’s social control through the saving mission of the Mental Hospital is implemented through the nursing practice and the controlling mechanism it performs in which the authority of the medical doctors is dominant enough to show that they have power in the Mental Hospital.